The Pursuit of International Students in a Commercialized World - Altbach, Philip; Reisberg, Liz (International Higher Education, 2013)
The use of agents and recruiters are increasingly common by universities to attract international students. This article focuses on some of the criticisms and problems related to agents and recruiters, and points to ways that universities and governments can best serve their own needs as well as the needs of prospective students.